Sosialisasi Pengelolaan Sampah sebagai Implementasi Mata Kuliah Ekologi Budaya Bagi Mahasiswa Fakultas Ilmu Budaya Universitas Halu Oleo - Mursin Mursin; Zulzaman Zulzaman; Hardin Hardin (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Waste management socialization is one form of implementing the Ecology course learning that aims to connect students' theoretical understanding with real practice in the community. This activity is carried out in response to increasing environmental problems due to the continuously growing volume of waste and the community's limited knowledge about sustainable management patterns. Through the socialization program, students apply ecological concepts such as material recycling, sustainability principles, the interrelationship of organisms with their environment, and the impact of human activities on ecosystems. The socialization is conducted using interactive lectures, group discussions, demonstrations of separating organic and inorganic waste, and simple compost-making practices. This participatory approach is designed so that the community not only understands the theory but is also able to practice it in daily life. The results of the activities show an increase in public knowledge and awareness about the importance of waste management from the source, including efforts to reduce single-use plastic, implement household waste sorting, and process organic waste into compost. In addition, these activities help build collective motivation to maintain environmental cleanliness, create healthier living spaces, and support the development of environmentally friendly behaviors. For students, these activities provide hands-on experience in applying ecological theory while enhancing communication, collaboration, and environmental analysis skills. Thus, waste management socialization not only contributes positively to the community but also strengthens the quality of ecological education as a relevant and practical science in addressing contemporary environmental issues.